Antibacterial Activity of Marine Sponge (Stylotella sp.) - Ni Komang Tri Dharmayani; Isnaini; Maria Ulfa; Sudirman; Emmy Yuanita; Baiq Nila Sariningsih (Jurnal Penelitian Pendidikan IPA, 2023)
Sponges are marine biota that makes up coral reefs that live on the bottom of the waters and have an important role in marine ecosystems. Sponges have bioactive components that have not been widely used by the community. This study aimed to analyze the content of secondary metabolites and the antibacterial activity of the sponge Stylotella sp. antibacterial activity test against Gram-negative (-) Escherichia coli and Gram-positive (+) Staphylococcus aureus was carried out using the good diffusion method. The results of antibacterial testing with various concentrations of 50, 100, and 150 ppm of the isolates showed that the zone of inhibition against E. coli was 11.3; 12; and 13 mm while for S. aureus was 12.3; 13; and 14 mm. The results of antibacterial testing with a concentration of 600 ppm of sponge extract showed an inhibition zone on E. coli and S. aureus in the amount of 13.3 and 14 mm, respectively. The test results showed that the sponge extract and isolate were in the intermediate category and were resistant to E. Coli bacteria. and S. Aureus